Perlindungan Konsumen Terhadap Penyebaran Informasi Menyesatkan Yang Disampaikan Melalui Iklan - Aulia, Elvita Septavianty; Sanggup Leonard Agustian; Fajar Sugianto (Faculty of Law-Universitas Bandar Lampung, 2025)
Advertising is a form of communication delivered by business actors to fulfill marketing functions. Advertising is one of the most effective communication mediums to promote a product, so that the product has a high selling value. However, many business actors promise advantages from excessive product use. Often the information conveyed does not match the actual condition of the product. Information conveyed through electronic media, print media and other promotional media must comply with the provisions of the Indonesian advertising code of ethics which emphasizes that information conveyed through advertising must be true, clear, honest and appropriate and imbued with a sense of healthy competition, and not excessive and meet other methods. However, these provisions are often ignored by business actors who want to make large profits through advertising and cause losses to consumers. The problems in this study are: (1) How is the regulation of responsibility for the dissemination of misleading information reviewed from Indonesian laws and regulations? (2) How are the efforts to resolve consumer disputes carried out by business actors over the spread of misleading information conveyed through advertising? By using normative research methods and legal approaches, it is known that: (1) The regulation of the responsibility of business actors for the suitability between the information conveyed through advertisements and the specifications and conditions of the products being traded has weaknesses. Laws and Regulations in Indonesia have not regulated the responsibility of business actors for the spread of misleading information conveyed through advertisements with the condition of the product received by consumers; and (2) Dispute resolution can be divided into two, namely outside the court and in court and there has been no certainty and legal justice for consumers in trusting product information conveyed through advertising.